Delirium due to Anticholinergic Intoxication and Use of Physostigmine in Pediatric Emergency Room - Alper Çiçek; Pelin Elibol; Şefika Bardak; Oğuz Demiroğlu; Gülşah Demir; Tuğçe Nalbant; Gamze Gökalp; Emel Berksoy (Galenos Yayinevi, 2022)
Anticholinergics are substances that antagonize the activity of the neurotransmitter acetylcholine. Anticholinergic syndrome (AS) occurs following a suicidal overdose, accidental drug intake, drug incompatibilities, and intake of multiple drugs simultaneously. Herein, we present two patients who were brought to the emergency room in a delirium state and were diagnosed with AS, presented other symptoms of anticholinergic toxidrome, and were treated with physostigmine.